INTEGRATED ARTIFICIAL IMMUNE SYSTEM AND TAGUCHI APPROACH FOR PRODUCTION SCHEDULING IN THE GARMENT INDUSTRY - Wang, Chia-Nan; Nguyen, Tram Thi Mai (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
Presently, Vietnam is the third-largest garment exporter in the world, with a 6.1% market share. Nevertheless, Vietnam's apparel industry faces fierce competition from other countries making low-cost garments. Enterprises must enhance many aspects to survive in a competitive market, including ensuring product availability at optimal prices. To achieve this, all production managers shall schedule production while factoring in early and late production costs. This study presents a novel integer nonlinear programming model to minimize the cost of earliness and tardiness, considering weight for storage. The metaheuristic utilized to solve the problem in this work is the integrated artificial immune system (AIS) algorithm and the Taguchi technique. Subsequently, implementing a sensitivity analysis to ascertain the weight for storage is a crucial decision faced by production managers. Finally, this study compares the proposed method to the Vietnamese garment industry's current technique and shows its suitability for production scheduling in this sector.